Dispersity, mesoporous structure and particle size modulation of hollow mesoporous silica nanoparticles with excellent adsorption performance. Issue 38 (2nd July 2018) - Tao, Guiju; He, Wenjun; Wang, Yu; Yu, Fengping; Ge, Junwei; Yang, Weimin
Abstract : Hollow mesoporous silica nanoparticles with different dispersities, mesoporous structures and particle sizes, and excellent adsorption performance have been systematically synthesized. Abstract : Hollow mesoporous silica nanoparticles (HMSNs) with different dispersities, mesoporous structures and particle sizes have been systematically synthesized by simply changing the octadecyltrimethoxysilane (C18 TMS, mesopore-forming agent) percentage of the total silica sources over a wide range. The effects of the C18 TMS percentage on the dispersity, mesoporous structure and particle size of HMSNs have been discussed in detail based on elaborate structure characterization. In addition, the volume of the core-etching agent and etching time have been adjusted carefully to further modulate the mesoporous structure of HMSNs. Encouragingly, the obtained HMSNs show excellent performance in removing organic pollutants with short equilibrium adsorption time, high adsorption capacity and outstanding recyclability. It is believed that these prepared HMSNs with different dispersities, mesoporous structures and particle sizes possess the potential to be used in many fields.